Rational design of heterodimeric receptors capable of activating target signaling molecules - Tatphon Kongkrongtong (Nature Portfolio, 2021)
Abstract Intracellular signal transduction is regulated by a variety of transmembrane receptors. Many researchers have aimed to arbitrarily regulate the intracellular signaling and subsequent cell fate with artificial receptors, of which the ligand recognition and signaling properties could be artificially designed. Although several architectures of homodimeric artificial receptors have been reported, engineering of heterodimeric receptors, which are abundant among natural receptors, have yet to be thoroughly investigated. In this study, we rationally design artificial heterodimeric receptors for activating target signaling molecules. We locate a tyrosine motif on an engineered tyrosine kinase domain, which is further connected to a small molecule-responsive heterodimeric module, attaining a pair of heterodimeric receptors with different tyrosine motifs within the pair. The resultant heterodimeric receptors successfully activate target signaling molecules and even control cell proliferation levels according to the properties of tyrosine motifs connected. Thus, our heterodimeric receptors may open a new era of tailor-made designer receptors, which could be useful for cell therapy against intractable diseases.